Characterizing the HIV risks and potential pathways to HIV infection among transgender women in Côte d'Ivoire, Togo and Burkina Faso. (17th July 2016) - Stahlman, Shauna; Liestman, Benjamin; Ketende, Sosthenes; Kouanda, Seni; Ky‐Zerbo, Odette; Lougue, Marcel; Diouf, Daouda; Anato, Simplice; Tchalla, Jules; Bamba, Amara; Drame, Fatou Maria; Ezouatchi, Rebecca; et al.
Abstract : Introduction: Transgender women are at high risk for the acquisition and transmission of HIV. However, there are limited empiric data characterizing HIV‐related risks among transgender women in sub‐Saharan Africa. The objective of these analyses is to determine what factors, including sexual behaviour stigma, condom use and engagement in sex work, contribute to risk for HIV infection among transgender women across three West African nations. Methods: Data were collected via respondent‐driven sampling from men who have sex with men (MSM) and transgender women during three‐ to five‐month intervals from December 2012 to October 2015 across a total of six study sites in Togo, Burkina Faso and Côte d'Ivoire. During the study visit, participants completed a questionnaire and were tested for HIV. Chi‐square tests were used to compare the prevalence of variables of interest between transgender women and MSM. A multilevel generalized structural equation model (GSEM) was used to account for clustering of observations within study sites in the multivariable analysis, as well as to estimate mediated associations between sexual behaviour stigma and HIV infection among transgender women. Results: In total, 2456 participants meeting eligibility criteria were recruited, of which 453 individuals identified as being female/transgender. Transgender women were more likely than MSM to report selling sex to a male partner within the past 12 months ( p< 0.01), to be living with HIV ( p< 0.01) and to report greater levels of sexual behaviour stigma as compared with MSM ( p< 0.05). In the GSEM, sexual behaviour stigma from broader social groups was positively associated with condomless anal sex (adjusted odds ratio (AOR)=1.33, 95% confidence interval (CI)=1.09, 1.62) and with selling sex (AOR=1.23, 95% CI=1.02, 1.50). Stigma from family/friends was also associated with selling sex (AOR=1.42, 95% CI=1.13, 1.79), although no significant associations were identified with prevalent HIV infection. Conclusions: These data suggest that transgender women have distinct behaviours from those of MSM and that stigma perpetuated against transgender women is impacting HIV‐related behaviours. Furthermore, given these differences, interventions developed for MSM will likely be less effective among transgender women. This situation necessitates dedicated responses for this population, which has been underserved in the context of both HIV surveillance and existing responses.